Teoria econômica, finanças e empresas de capital aberto: uma análise corporativa de empresas - Abreu, Paola Zanluchi [UNESP] (2010)
The study attempts to develop the concept of financial fragility and explore the advancement of their chances, since he started in 1970 until the present day with the most respected authors. The analysis focuses on the possibility of changing the cycle of economic activity that is due to the vulnerability, and so that it is related to the behavior of firms and agents. What can be done to prevent such a crisis. Thus, the authors present the factors and explain how the credit market, operating assets and investments of capital goods under the influence in that economy. It also consists in the analysis to visualize the size of the influence of credit, interest and investments made by the evaluation of a data set